Food Industry - Muzzalupo, Innocenzo (IntechOpen, 2013)
Due to the increase in world population (more than seven billion inhabitants) the global food industry has the largest number of demanding and knowledgeable consumers. This population requires food products that fulfill the high quality standards established by the food industry organizations. Food shortages threaten human health, and also the disastrous extreme climatic events make food shortages even worse. This collection of articles is a timely contribution to issues relating to the food industry. The objective of this book is to provide knowledge appropriate for students, university researchers, and in general, for anyone wishing to obtain knowledge of food processing and to improve the food product quality.